Design and simulation of an accelerometer with improved sensitivity response (2016)
(Eng) The capacitive accelerometers based on microelectromechanical systems (MEMS), are widely used in the automotive industry, in seismic detection, and in military applications. The sensitivity is one of their main characteristics, which widely benefit their use in front of small acceleration changes. In this work, the elements considered in the analyses of these systems are mass and suspension beams, which constitute a mass-spring system. The mathematical modelling establish its mechanical response. Based on the equations of sensitivity and frequency of displacement response sets out the criteria to determine the geometry of the mass and the length of suspension beams are obtained in order to improve the sensitivity response. The importance of the stiffness constant is also considered as part of the design. In this case, the changes in the mass produces irregular geometries that, at the same time, allows to increase the beam’s length. The improvement in the sensitivity value permits the actuation at lower levels of acceleration. In addition, the simulation of the vibration mode, corresponding to the in-plane displacement, is carried out with the purpose of determining the appropriate frequency for the system operation. Material used for the actuator implementation is silicon. ANSYS is the software used to carry out simulations and characterization of the analyzed systems.